Late antique letter collections : a critical introduction and reference guide - Sogno, Cristiana, 1969-; Storin, Bradley K.; Watts, Edward Jay, 1975- (Joan Palevsky imprint in classical literature., 2016)
"This volume provides the first comprehensive overview of the extant Greek and Latin letter collections of late antiquity (ca. 300-600 C.E.). Bringing together an international team of historians, classicists, and scholars of religion, it illustrates how letter collections advertised an image of the letter writer and introduces the social and textual histories of each collection. Each chapter addresses a major collection of Greek or Latin literary letters, examining their assembly, publication, and transmission. In addition, contributions reveals how late antique letter collections operated as a discrete literary genre with its own conventions, transmission processes, and self-presentational agendas. This book will fundamentally change how people both read these texts and use letters to reconstruct the social history of the fourth, fifth, and sixth centuries"--Provided by publisher